Factors influencing the quality of life of patients with disability post stroke in Mopani District, Limpopo Province - Langa, Mmabatho (My University, 2018)
Background: Recent studies suggest that many people are faced with long term disability as a result of the increase in the incidence of stroke in South Africa. Currently there is no knowledge on the factors that influence the quality of life of stroke patients in Mopani District. As a result, it is difficult to plan rehabilitation for the patients. This study aims to determine the factors influencing the quality of life of patients with disability post stroke in Mopani District, Limpopo. Methods: A quantitative, descriptive cross-sectional research design was used. A total of 231 participants out of a sample size of 341 was purposefully selected from five public hospitals in Mopani district and took part in the study. This resulted in a response rate of 68%. Data were collected using a questionnaire and the Stroke Specific Quality of Life Scale (SSQOL). Data were analysed using STATA version 13 and open- ended questions were analysed quantitatively using summative content analysis. Results: The majority of the participants were black, female, single and had completed secondary school education. Most of the participants reported to have good quality of life (66%). Thirty five percent of the participants however expressed that they were more dependent on their caregivers as well as their need to be more self-reliant. Age, marital status and source of livelihood had a highly significant relationship with QOL (P-value of 0.001, 0.003 and 0.008 respectively). The domains which participants scored poorly were work, upper extremity function, social and family roles. Participants with poor quality of life had the following scores: work (33%), social (32%), upper limb function (44%) and family roles (40%). Participants with good quality of life scored: work (60%), upper extremity function (64%), social (60%) and family roles (67%). Conclusion: The study findings indicate that rehabilitation should focus on acquiring optimal physical ability as well as obtaining social integration. The research has identified challenges that can lead to dissatisfaction with quality of life amongst stroke survivors who are independent in daily activities. Keywords: Stroke, Quality of life, activities of daily living, caregiver, rehabilitation, rural.
A research report submitted to the school of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Public Health in the field of Rural Health, August 2018